Parameters of the airflow when exiting the fan - Xalilov Muxtor; Fayzullaev Khayriddin (E3S Web of Conferences, 2023)
The purpose study is to substantiate the parameters of the air flow when exiting the casing and the working parts fan. In the course of studies, the pressure and air flow velocity were determined by an improved Pitot-Prandtal tube. In experimental studies, the influence speed fan wheel improved sprayer on the parameters air flow when exiting the window casing and the working part was studied. It was found that the pressure air flow from the window fan casing increases on average from 65 Pa to 152 Pa when the number of revolutions wheel is increased from 800 r/min to 1200 r/min, and 5.5 times when the number of revolutions is increased from 800 r/min to 1600 r/min. The speed air flow coming out window shroud fan depends on the pressure, it was observed that the speed increased by 2.5 times when the pressure in the system increased from 100 to 350 Pa. According to the results studies carried out, in order to ensure high-quality chemical processing with low energy consumption, the number of revolutions centrifugal fan wheel should be equal to 1500 r/min.